Low versus high dialysate calcium concentration in alternate night nocturnal hemodialysis: A randomized controlled trial. Issue 1 (30th June 2016) - Masterson, Rosemary; Blair, Susan; Polkinghorne, Kevan R.; Lau, Kenneth K.; Lian, Michael; Strauss, Boyd J.; Morgan, John G.; Kerr, Peter; Toussaint, Nigel D.
Abstract: Introduction: Higher calcium dialysate is recommended for quotidian nocturnal hemodialysis (NHD) (≥6 nights/week) to maintain bone health. It is unclear what the optimal calcium dialysate concentration should be for alternate night NHD. We aimed to determine the effect of low calcium (LC) versus high calcium (HC) dialysate on cardiovascular and bone parameters in this population. Methods: A randomized controlled trial where participants were randomized to LC (1.3 mmol/L, n = 24) or HC dialysate (1.6 or 1.75 mmol/L, n = 26). Primary outcome was change in mineral metabolism markers. Secondary outcomes included change in vascular calcification (VC) scores [CT abdominal aorta (AA) and superficial femoral arteries (SFA)), pulse wave velocity (PWV), bone mineral density (BMD) and left ventricular mass index (LVMI) over 12 months. Findings: In the LC group, pre‐dialysis ionised calcium decreased −0.12 mmol/L (−0.18–0.06, P = 0.0001) and PTH increased 16 pmol/L (3.5–28.5, p = 0.01) from baseline to 12 months with no significant change in the HC group. In both groups, there was no progression of VC in AA or SFA and no change in PWV, LVMI or BMD. At 12 months, calcimimetics were prescribed in a higher percentage in the LC vs. HC groups (45.5% vs. 10.5%) with a lower proportion of the HC group being prescribed calcitriol (31.5% vs. 72%). Discussion: Although dialysate calcium prescription influenced biochemical parameters it was not associated with difference in progression of VC between HC and LC groups. An important finding was the potential impact of alternate night NHD in attenuating progression of VC and inducing stabilisation of LVMI and PWV.